Proapoptotic role of CDK1 in overcoming paclitaxel resistance in ovarian cancer cells in response to combined treatment with paclitaxel and duloxetine - Gyeongmi Kim; Se-Kyeong Jang; Se Hee Ahn; Selim Kim; Chan Sub Park; Min-Ki Seong; Hyun-Ah Kim; Seunghee Bae; Jae Ho Lee; Hyunggee Kim; Hyeon-Ok Jin; In-Chul Park (Cancer Cell International)
Abstract Background Paclitaxel resistance and recurrence are major obstacles in ovarian cancer, which is the leading cause of death among gynecologic cancers. During cancer cell progression, cyclin-dependent kinase 1 (CDK1) drives cells through the G2 phase and into mitosis. In this study, we demonstrated that CDK1 played a crucial role in switching paclitaxel-resistant ovarian cancer cells from mitotic arrest to apoptosis following combined treatment with paclitaxel and duloxetine, an antidepressant known as a serotonin-norepinephrine reuptake inhibitor (SNRI). Methods Cell viability was assessed by MTT assay. Apoptotic cell death and mitochondrial membrane potential (MMP) were detected by flow cytometry. Protein expression levels were explored using western blotting. Mitochondrial and cytosolic fractionation were performed to determine the mitochondrial localization of proteins. Immunofluorescence was used to detect protein expression levels and localization. Results Combined treatment with paclitaxel and duloxetine induced apoptotic cell death in paclitaxel-resistant ovarian cancer cells. We suggested that combined treatment of these drugs induced CDK1 activation and increased mitochondrial localization of activated CDK1, which caused phosphorylation of the antiapoptotic Bcl-2 and Bcl-xL proteins. Selective CDK1 inhibitors blocked Bcl-2 and Bcl-xL phosphorylation induced by paclitaxel and duloxetine, and strongly suppressed apoptotic cell death. Furthermore, we demonstrated that S6K is a potential upstream mediator of the proapoptotic activation of CDK1. Conclusion Taken together, switching CDK1 to a proapoptotic role through the combination of paclitaxel and duloxetine could overcome paclitaxel resistance in ovarian cancer cells, providing promising therapeutic strategies for treating paclitaxel-resistant ovarian cancer.